Investigation of the Effects of Light, Darkness, and Dim Light on Rat Brain Tissue: A Biochemical and Histological Study - Pekmez, Hidir; Raika Kiran, Tugba; Tecellioglu, Fahriye Seccommail; Inceoglu, Feyza; Aydin, Merve; Zayman, Emrah; Canpolat, Sinan (Amer Chemical Soc, 2025)
This study evaluates acetylcholinesterase (AChE) enzyme activity levels, oxidative stress parameters, histopathological findings, and serum melatonin levels in rat brain tissue. 32 male Wistar Albino rats were randomly divided into four groups: Control, Light, Dark, Dim light (n = 8 each group). After a 30 day experiment, brain tissues were collected to measure AChE, glutathione S-transferase (GST), glutathione (GSH), and malondialdehyde (MDA) levels and conduct histopathological analyses. Serum melatonin levels were also measured. In this study, we observed a significant increase in MDA levels in dim light, dark, and light groups. AChE and alpha-GST enzyme activity levels were significantly decreased in the dark group compared with the other groups. Additionally, there was a statistical difference in melatonin levels between the light and dark groups. In the light microscope examination of the sections stained with hematoxylin-eosin from the dark group brain tissue, mild perineuronal edema was observed in all areas. Our study is the first to compare the effects of three groups on the brain: continuous light, continuous darkness, and dim light at night. Additionally, it is the only study to examine the effects of light exposure differences on the brain AChE levels.
Keywords: light; dark; dim light; ache